(untitled) (Mayéutica Revista Científica de Humanidades y Artes, 2018)
The so-called "Carta de Jamaica" is one of the most important documents of the Political Thought of Hispanic-American Emancipation, which arrived in 2015 two hundred years after being written by the Liberator Simón Bolívar. The purpose of this essay is to study the historical conditions that gave rise to this document, which we tackled as the Political Project of Bolívar in the struggle for Independence and Hispanic American Emancipation. In that sense, after characterizing the political situation that was lived in Europe and America and reviewing the state in which the military forces were fighting in Venezuela and New Granada in 1815, we tried to explain the geopolitical reasons that led to Bolivar to go to Jamaica, his activities in favor of the independence cause in that island under English rule, to finally analyze - in that context - the arguments presented by the Liberator and his projection in the history of Latin American and Caribbean political thought to two hundred years of its writing.